Post-Resuscitation Syndrome: A Multidisciplinary Approach To Therapy - Toshev Izzat Ikromovich (Genius Journals, 2025)
Postresuscitation syndrome (PRS) remains one of the most pressing issues in modern resuscitation and intensive care. Its pathogenesis includes a complex of hypoxic -ischemic, reperfusion , inflammatory and metabolic disorders leading to multiple organ dysfunction in patients after successful cardiopulmonary resuscitation. The main causes of circulatory arrest were acute coronary pathologies and cardiac arrhythmias. The most pronounced clinical manifestations included hypoxic encephalopathy, myocardial dysfunction, infectious complications and metabolic disorders. Complex therapy using targeted temperature therapy, hemodynamic stabilization, nutritional support, infection prevention, cardiological and neurological correction, as well as early rehabilitation has demonstrated a positive effect on treatment outcomes. The importance of a multidisciplinary approach to managing patients with PRS aimed not only at survival but also at restoring quality of life is emphasized. The obtained data are consistent with current international recommendations (AHA, ERC, ESICM, ILCOR) and highlight the need for further research in this area
Keywords: post-resuscitation syndrome; cardiac arrest; resuscitation